Exploring the school leaders’ sense of school belongingness through systematic grounded theory - Padhan, Goutam (Journal of Interdisciplinary Studies in Education, 2026)
This study aims to explore school leaders’ sense of school belongingness from the ground. To achieve the study objectives, grounded theory methodology was employed. The research began with purposive sampling and ended with the use of theoretical sampling techniques. Data were analysed according to the mandated norms of the systematic grounded theory. Consequently, a leader's sense of belonging is linked to their management of power dynamics within the school, characterized by their contribution. Work tenacity and proactive behaviours are indicators of a leader's sense of belonging. Subsequently, an (NE)3 framework was developed based on a literature review, which validated the study’s results. In conclusion, leaders’ sense of belonging is a motivating factor for promoting leadership to improve schools.